A glycine- and glutamate-rich protein is female salivary gland-specific and abundant in the malaria vector Anopheles dirus B (Diptera: Culicidae) - Narissara Jariyapan (2018)
Before transmission, malaria parasites reside in the salivary glands of their female mosquito hosts. Saliva proteins assist in blood feeding and also may influence the ability of mosquitoes to transmit malaria. We attempted to identify and isolate cDNAs encoding proteins expressed at a high level in the salivary glands of a malaria vector, Anopheles dirus B Peyton & Harrison (=An. cracens) (Diptera: Culicidae). A major protein with an estimated molecular mass of 35 kDa and an isoelectric point (pI) of ≈4 was detected on a two-dimensional (2D) gel. Internal peptide sequences of the protein spot showed high similarity to sequences present in the conserved C-terminal domain of glycine- and glutamate (GE)-rich proteins. A full-length cDNA encoding this protein was isolated from a salivary gland cDNA library of female An. dirus B. The cDNA encoded a 256-residue protein with a calculated molecular mass of 25.4 kDa and a pI of 3.9. BLAST analysis confirmed that it is a member of the GE-rich family. Compositional and sequence analysis of this and other family members revealed a highly acidic N-terminal region of variable length and low sequence conservation and a well conserved C-terminal domain containing 10 identical residues across the 13 known members of the gene family in mosquitoes. The An. dirus B GE-rich transcript was detected by reverse transcription-polymerase chain reaction (PCR) only in the female salivary glands, indicating that this protein is female saliva-specific. The GE-rich proteins may function as a salivary lubricant to facilitate blood feeding. © 2006 Entomological Society of America.